Confronting Challenges Facing Teachers in Implementing CompetencyBased Curriculum in Uganda: A Case of Secondary Schools in Gulu City - Kidega, Charles; Song, Zheng; Ugochinyere, Ibeakamma Chinazaekpere; Okwel Aria James; Ndikubwimana, Faustin (East African Journal of Education Studies, 2024)
his paper investigated the challenges facing teachers in implementing a competence-based curriculum in secondary schools in Uganda. The study employed a qualitative research approach that utilised a case study research design. The sample of the study included 50 teachers who were randomly selected, 4 heads of schools, and 4 education officers who were purposefully selected from 4 public secondary schools found in Gulu City, Uganda. Observations and interviews were used to collect the required information. The findings established that teachers faced a variety of challenges that impeded the effective implementation of a competence-based curriculum in teaching and learning. The researcher also noticed that teachers face a big problem in the implementation of competency-based curricula: insufficient training of teachers and limited engagement of teachers in workshops and seminars that would help enrich them with some skills. So, in a sense, the implementation of CBC started without enough teacher training. Poor infrastructure in schools, limited numbers of housing facilities for teachers, no recommended teaching materials given to teachers, too many students in the classroom, and high computer illiteracy rates among teachers limited the success of CBC implementation in Uganda, especially in government-aided secondary schools. Based on the results of the study, the researcher recommended the following strategies to improve the implementation of CBC in secondary schools in Uganda: revamping teacher professional development; in order to effectively facilitate learning and engage with contemporary learners, teacher educators must be with teaching teachers; establish a robust plan for ongoing constructive interactions by NCDC with all other stakeholders; provide timely resources; and invest enough in schools so that they can deliver the right curriculum. Ensure regular inspection; the inspection role should be equipped to ensure the consistency of the curriculum. Teachers should encourage and practice more project-based learning and also harmonize and implement the language of instruction and evaluation policy clearly to avoid confusion among teachers